Regional Economic Outlook, October 2017, Sub-Saharan Africa. (Regional Economic Outlook, 2017)
Growth in sub-Saharan Africa has recovered relative to 2016, but the momentum is weak and per capita incomes are expected to barely increase. Further, vulnerabilities have risen in many countries, adding to the urgency of implementing the fiscal consolidations planned in most countries and with stepped up efforts to strengthen growth.